2014
DOI: 10.1073/pnas.1322291111
|View full text |Cite
|
Sign up to set email alerts
|

How blebs and pseudopods cooperate during chemotaxis

Abstract: Two motors can drive extension of the leading edge of motile cells: actin polymerization and myosin-driven contraction of the cortex, producing fluid pressure and the formation of blebs. Dictyostelium cells can move with both blebs and actin-driven pseudopods at the same time, and blebs, like pseudopods, can be orientated by chemotactic gradients. Here we ask how bleb sites are selected and how the two forms of projection cooperate. We show that membrane curvature is an important, yet overlooked, factor. Dicty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
114
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 34 publications
13
114
1
Order By: Relevance
“…The same mechanism could also explain the experimental observation that blebs are nucleated preferentially in regions of negative membrane curvature [43]. Changes in osmotic pressure gradients could also contribute to the process, as suggested previously [13,20,44], but are not explicitly included in our model.…”
Section: Experimentsupporting
confidence: 59%
“…The same mechanism could also explain the experimental observation that blebs are nucleated preferentially in regions of negative membrane curvature [43]. Changes in osmotic pressure gradients could also contribute to the process, as suggested previously [13,20,44], but are not explicitly included in our model.…”
Section: Experimentsupporting
confidence: 59%
“…Beside cortical tension [26,34], loss of cellular adhesion has been discussed as a potential reason for membrane blebbing [31]. Moreover, the impact of membrane curvature has been shown to influence bleb formation in dictyostelium [35]. All these mentioned parameters could potentially play a role in the experiments of this study, as a reduced spreading area on 1D tracks was observed (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, actively migrating PGCs exhibit membrane blebbing in Drosophila melanogaster embryos (2). Dictyostelium use membrane blebbing during chemotaxis (3,4). Thus, membrane blebbing is widely used as a driving force of motility across species (4,5).…”
mentioning
confidence: 99%
“…Dictyostelium use membrane blebbing during chemotaxis (3,4). Thus, membrane blebbing is widely used as a driving force of motility across species (4,5). In addition, cancer cells use a membrane blebbing-associated mode of motility in metastasis (6).…”
mentioning
confidence: 99%